CALON GURU PAUD DAN TANTANGAN MASA DEPAN: TEMUAN AWAL PANDANGAN MAHASISWA TENTANG PENDIDIKAN ABAD 21 - Ali Formen (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
Many have argued that early childhood education (ECE) is an investment for a better future. This claim perhaps is valid only if today’s ECE corresponds with the imagined future. Among the images of the future our education system promotes are the so-called 21st-century skills and their prerequisites, 21st-century education/learning. To further unpack today's ECE link with the intended future, this article presents dataset on ECE teacher candidates’ views about 21st-century skills, education, and learning. Sixty-one students of a Central Java-based university voluntarily participated in the study. Through an online questionnaire, they reported their knowledge about 21st-century education and readiness to become a 21st-century teacher. Nevertheless, their responses seem to disconnect from the literature on 21st-century education. Although not generalizable, these findings are critical for ensuring today’s teacher training alignment with the idea of ECE as an investment for a better future.